2022
DOI: 10.51253/pafmj.v72i4.7212
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease Investigation with Marsh Classification in Paediatric Population

Abstract: Objective: To determine the celiac disease using Marsh classification in the paediatric population at the Pak Emirates Military Hospital. Study Design: Cross-sectional study. Place and Duration of Study: Department of Paediatrics, Pak Emirates Military Hospital Rawalpindi Pakistan, from Aug 2020 till Mar 2021. Methodology: Patients of either gender aged 1 to 14 years with three or more clinical features of celiac disease such as chronic diarrhoea, any degree of malnutrition, short stature, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the Iranian series, biopsy showed that 90.4% of the studied population had villous atrophy of varying degrees [ 89 ], and histologic examination also showed atrophy in 92% of cases [ 90 ]. In contrast, a study from the United Arab Emirates showed histologic positivity in only 57.7% of cases [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Iranian series, biopsy showed that 90.4% of the studied population had villous atrophy of varying degrees [ 89 ], and histologic examination also showed atrophy in 92% of cases [ 90 ]. In contrast, a study from the United Arab Emirates showed histologic positivity in only 57.7% of cases [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous studies, questions regarding delayed diagnosis remain unanswered [ 78 ]. In our context, possible explanations for the delay in diagnosis are (1) The erroneous belief that CD is rare and pediatric [ 91 , 98 , 99 ]; (2) lack of awareness of the variability of clinical presentation [ 37 , 75 , 85 , 91 ]; (3) difficulty of access to care in developing countries [ 45 , 57 , 100 , 101 ]; (4) lack of screening in at-risk individuals [ 58 , 75 , 85 ], and the nutritional and epidemiological transition that is currently undergoing in Morocco [ 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in pediatric patients (under 14 years), the diagnosis was based solely on positive serological tests. In the current study, duodenal biopsy samples were assessed by a pathologist following the guidelines of Marsh's classification system [ 13 ], evaluating the presence of villous atrophy, crypt hyperplasia, and other histological features. Marsh stage 2 and above were considered positive.…”
Section: Methodsmentioning
confidence: 99%